Role of Veterinary Science in Human Wellness - Patel, B. H.M.; Kumari, Anjali (Indian Farming, 2015)
Animals are an important part in human life. Keeping the role of animals in human wellness, it is always our moral duty to take care of animals through good welfare practices.